Social entrepreneurship in higher education institutions in Malaysia: conceptual framework - Mohammad, Noorita; Asnawi, Nini Hartini; Ghazali, Norfazlina; Salleh, Nor Fazalina; Mohammad, Mardhiah; Putit, Lennora (Penerbit UiTM, 2022)
The implementation of educational policies is often related to entrepreneurs. Social entrepreneurship policies have become the newest phenomenon in Malaysia in the country’s attempts to reduce and eradicate poverty. Until today, there is limited knowledge on how social entrepreneurship can become a catalyst for a community’s economic advancement and closing the social gaps within the society. This paper aims to explain further and provide knowledge regarding social entrepreneurship as a strategy to enhance national higher education policies. Through extensive literature analysis, social entrepreneurship is placed within the context of higher education institutions in implementing ethical and moral values. This conceptual framework encompasses the concept of economic development, social development of a community, social entrepreneurship principles, the less fortunate, and the role of the suggested higher education institution. This paper will contribute to future literature regarding social entrepreneurship and can help the entrepreneurial system as they establish social enterprises based on real solutions for communities. The results of this research are expected to assist various parties, such as academics, policymakers, social entrepreneurs, government and private companies, and the community, in better understanding social entrepreneurship. It will also spread the impact of social entrepreneurship into the existing social entrepreneurial education system in Malaysia. Therefore, the discussions around the social entrepreneurship model will measure whether social entrepreneurship has been carried out to its fullest according to the fundamental concept of overcoming and helping solve social problems, exceptionally the less fortunate.